An improved ring method for calibration of hydrometers - Mohd. Nor, Mohd. Fazrulhisyam (2014)
This study describes an improved hydrometer calibration method using a ring type sinker as a reference standard mass. Ring method offers simple yet effective hydrometer calibration method with comparable performance to other hydrometer calibration methods. This work also reports a ring method experimental setup for calibrating hydrometers. The theoretical calculation was developed and tested with experimental data. This calibration method can be used for any surface tension and reference temperature design of hydrometer. A suitable dimension of standard ring was used to sink hydrometers into distilled water. The distilled water was used as standard liquid, traceable to a standard solid density determined by hydrostatic weighing method. A tensiometer consisting of balance and Wilhelmy plate was used to measure the surface tension of the distilled water. The calibration results showed an improvement in the calibration range between 0.600 g mL-1 and 1.000 g mL-1 with an uncertainty of 0.0002 g mL-1 for hydrometers with scale graduations of 0.0005 g mL-1. The differences in measured scale corrections of this method compared to the comparison method and hydrostatic weighing method indicate a bias smaller than half of the hydrometer graduation. In comparison, this method offers simpler, cheaper calibration with accuracy comparable to other existing hydrometer calibration methods. Furthermore, no harmful chemicals were used as standard liquid especially mixtures of volatile hydrocarbons or aqueous solutions of acids.